Performance and stability of chitosan-MWCNTs-laccase biocathode: Effect of MWCNTs surface charges and ionic strength - El Ichi-Ribault, S; Zebda, A; Tingry, S; Petit, M; Suherman, A; Boualam, A; Cinquin, P; Martin, D (Elsevier, 2017)
A three-dimensional biocathode structure was fabricated by compacting chitosan, multiwall carbon nanotubes (MWCNTs) and laccase from Trametes versicolor in a mechanical press. The effect of functionalizing the MWCNTs with amine groups on the morphology, the electrocatalytic activity and the stability of the biocathode were evaluated for the direct and mediatorless oxygen reduction. The chemical groups bound to the MWCNTs surface influenced the interconnection of the chitosan nanofibers and consequently the surface area (SBET). Biocathodes based on pristine MWCNTs had a larger surface area compared with those made with functionalized MWCNTs. The direct electron transfer (DET) between the enzyme and all studied types of MWCNTs was demonstrated by the open circuit potential (OCP), cyclic voltammetry and chronoamperometry. The most efficient laccase immobilization was obtained for the biocathode with functionalized MWCNTs, whereas a better stability over time was measured when pristine MWCNTs were used. These results can be explained by the better stability of hydrophobic-hydrophobic interactions between laccase and pristine MWCNTs compared with ionic interactions in the case of functionalised MWCNTs which are very sensitive to ionic strength of the buffer solution. In the case of functionalised MWCNTs, laccase was desorbed by increasing salt concentration in the buffer, and it was re-adsorbed again by decreasing salt concentration in the buffer solution.